2014
DOI: 10.5194/gi-3-29-2014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of source of background noise in muon radiography using emulsion film detectors

Abstract: Abstract. The aim of this study is to ascertain and confirm the source of background noise in cosmic-ray muon radiography (muography) using emulsion film detectors. For this, we build two types of emulsion detectors with different momentum thresholds and perform test measurements of an actual geoscientific target. This experiment reveals that contamination of nonsignal particles with momenta of less than 2 GeV c −1 cause significant systematic errors for the density estimation of muography. Utilizing the resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…A study published in Nishiyama et al [] leads to very similar results to the MU‐RAY and TOMUVOL measurements presented here. That study used two emulsion‐based detectors with different momentum thresholds (0.2 and 2 GeV/c) and demonstrated that low‐energy particles dominate the background population.…”
Section: Discussionsupporting
confidence: 88%
“…A study published in Nishiyama et al [] leads to very similar results to the MU‐RAY and TOMUVOL measurements presented here. That study used two emulsion‐based detectors with different momentum thresholds (0.2 and 2 GeV/c) and demonstrated that low‐energy particles dominate the background population.…”
Section: Discussionsupporting
confidence: 88%
“…Studies and prospects for such kind of noise are well described in (Jourde et al . ; Nishiyama, Miyamoto, and Naganawa ).…”
Section: Muon Tomographymentioning
confidence: 95%
“…In the experiment described by Nishiyama et al . (), it turned out that the main background sources are low momentum particles. Since the ECC is one of the best tools to filter such background signal, it was used for both detectors at Teide and La Palma islands.…”
Section: Muon Tomographymentioning
confidence: 99%
“…Film-to-film alignment and track reconstruction were performed by using the FEDRA framework (Tioukov et al, 2006). We then performed our original track selection (Nishiyama et al, 2014). The signal tracks were selected on the basis of (i) number of hits, (ii) grain density and (iii) straightness of the reconstructed tracks.…”
Section: Track Selectionmentioning
confidence: 99%